LC-MS metabolic study on quercetin and taxifolin galloyl esters using human hepatocytes as toxicity and biotransformation in vitro cell model - Vacek, Jan; Papoušková, Barbora; Vrba, Jiří; Zatloukalová, Martina; Křen, Vladimír; Ulrichová, Jitka (Journal of pharmaceutical and biomedical analysis, 2013)
Galloyl esters of quercetin and taxifolin have been recently prepared semisynthetically as part of work towards modifying the solubility and modulating the biological activity of these natural flavonoids. In this paper we focused on the liquid chromatography-mass spectrometry (LC-MS) profiling of metabolites of 3-O-galloylquercetin and 7-O-galloyltaxifolin using human hepatocytes as the in vitro cell model. A subtoxic concentration (50μM) was used for both compounds and the formation of metabolites was monitored for 2h in hepatocytes and cultivation medium separately. Using negative electrospray ionization-quadrupole time-of-flight mass spectrometry (ESI-QqTOF MS), we identified different biotransformation patterns for the studied compounds. 3-O-Galloylquercetin is metabolized directly to glucuronides and methyl derivatives. In contrast, 7-O-galloyltaxifolin is oxidized to 7-O-galloylquercetin or cleaved to taxifolin, and consequently the products formed are sulfated or glucuronidated. The oxidative biotransformation of 3-O-galloylquercetin and 7-O-galloyltaxifolin is also accompanied by ester bond cleavage presumably by cellular enzymes (esterases) in a nonspecific manner. Our results provide fundamental insights into the biotransformation of monogalloyl esters of flavonoids and can be applied in investigations of the pharmaceutical potential of other galloylated polyphenolic substances.
Keywords: hepatocyty; Animals; ESI-QqTOF MS; 3-O-galloylquercetin glucuronide; quercetin; Female; HPLC; 3-O-galloylquercetin; Metabolic transformation; ženské pohlaví; electrospray ionization-quadrupole time-of-flight mass spectrometry; Tandem Mass Spectrometry; PHE; taxifolin glucuronide; Adolescent; Esters; TG; SIM; lidé; Mass spectrometry; Mice; Chromatography, Liquid; gallic acid (gallate); 3-O-galloylquercetin methyl derivative; 7-O-galloylquercetin; Mice, Inbred BALB C; kultivované buňky; 3GQM; myši; selected-ion monitoring; hmotnostní spektrometrie; Hepatocytes; buňky NIH 3T3; NIH 3T3 Cells; Taxifolin-7-O-gallate; TS; 3GQG; 7GQ; Cells, Cultured; taxifolin sulfate; kyselina gallová; Male; tandemová hmotnostní spektrometrie; myši inbrední BALB C; biotransformace; phenyl; 3GQ; liquid chromatography–mass spectrometry; Mass Spectrometry; Quercetin-3-O-gallate; estery; Biotransformation; high-performance liquid chromatography; lidé středního věku; 7-O-galloyltaxifolin; GA; Quercetin; zvířata; mužské pohlaví; 7GT; Gallic Acid; Middle Aged; mladiství; chromatografie kapalinová; Cytotoxicity; LC–MS; Humans